Measuring the digital economy in Czech republic - Jíra, Pavel; Tyll, Ladislav; Badie, Natálie; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This thesis addresses the challenge of measuring the digital economy's contribution to national economic performance, focusing on the Czech Republic. Traditional industry-sizing tools struggle to capture the pervasive nature of digital technologies across various sectors. Two primary methodologies were used: the Bureau of Economic Analysis (BEA) approach and the China Academy of Information and Communications Technology (CAICT) approach. The BEA method utilizes supply-use tables and relevant CPA3 categories to estimate the digital economy's direct contribution. The CAICT approach combines estimates of digital industrialization and industry digitization, incorporating capital use data for growth accounting. The analysis is supplemented by industry statistics for validation. The thesis finds that the digital economy's penetration in the Czech Republic accounts for 8.39% of the country's GDP following the BEA approach and 8.49% following the approach of CAICT. This research provides a framework for measuring the digital economy's size and significance and offering insights into its impact on national economic performance.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses